VISUAL DIGITAL MARKETING STRATEGY FOR BEST WESTERN PREMIER LA GRANDE HOTEL RESTAURANT IN BANDUNG - Mardiani Sukarana; Muhammad Anas (Universitas Negeri Makassar, 2021)
The problem that often occurs in the scope of hotel regulations is marketing, in the sense that hotel restaurants are still often located in hotels, both management and marketing. Hotel marketing is still dominated by basic facilities such as rooms and meeting rooms, so the marketing of the restaurant is less significant. This has an impact that the source of income from the restaurant is not able to meet the target. Therefore it is necessary to conduct research on how the role of hotels in promoting restaurants and how to implement visual digital marketing strategies in boosting restaurant publications. The purpose of this study is to reveal a marketing strategy that applies visual digital marketing by the managers of Best Western Premier La Grande in applying digital marketing with a creative human approach. The type of research used is field research, using a qualitative descriptive approach. The research produces descriptive data that analyzes the role of digital or online marketing at the Best Western Premier La Grande hotel. The results showed that the Best Western La Grande Hotel in Bandung implemented a marketing strategy based on creativity and used a digital marketing approach. This can be seen from the findings in the field that the Best Western Premier Bandung hotel has an online website which is located at http://bwpremierlagrande.com/ and Digital Brochure or E-brochure. In addition to supporting hotel marketing, these two contents also introduce the restaurant owned by the Best Western Premier Bandung hotel. The marketing creativity of the Best Western hotel and restaurant management team does not only stop at the website and e-brochure, the manager of the Best Western Premier Bandung Hotel through their public relations IT uses hashtags in the Instagram application, especially to introduce the restaurant. Some restaurant visitors are advised to take a photo of the dining menu and then upload it on Instagram with the hashtag Best Western Premier Bandung. With this hashtag, netizens will find it easier to get information quickly when looking for content related to hotels or restaurants.